Realist Needs Assessment Investigating the Factors Affecting Implementation of Guideline-Based Care for Chronic Pain in Rural Australia: Program Theory Generation - Ashley R Grant; Gill Westhorp; Amelia Mardon; Emma L Karran; Peter D Hibbert; Christopher Roeger; G. Lorimer Moseley (International Journal of Qualitative Methods)
We developed a realist program theory describing factors that affect healthcare professionals’ delivery of guideline-based pain care in rural Australia as part of a realist-informed needs assessment. To our knowledge, this project is the first to apply a realist research approach to conducting a needs assessment. We conducted and analysed realist informed teacher-learner cycle interviews with rural healthcare professionals to inform our program theory. In these interviews, we presented participants with a summary of guideline recommendations for the assessment and management of chronic pain. We asked participants which recommendations they found easy and challenging to implement in their local setting, and discussed why, how, and in what circumstances this was the case. We detail how we analysed interview transcripts retroductively in NVivo and how the authorship team abstracted from the clinical scenarios provided by interviewees to generate theories at a ‘middle level’ of abstraction. Our discussion details lessons learned from the utilised methods with recommendations for how we would adapt these methods in the future.